Authentication of Averrhoa carambola L. Using DNA Barcoding: Detection of SNPs and Evaluation of Phylogenetic Relationship - Giri, Alok Kumar; Biswal, Bhagyashree; Jena, Biswajit; Acharya, Laxmikanta (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Averrhoa carambola L. (star fruit) is an underutilized plant in the family Oxalidaceae. The plant has various pharmacological activities and has fleshy juicy fruit with high nutritional value and is rich in vitamins. Objectives: This study aims to authenticate and examine the evolutionary relationships between various Averrhoa taxa. Materials and Methods: The species identification was verified using the well-established DNA barcoding method. For this, a few predetermined loci including rpoB, matK, atpF-atpH, and rbcL were employed. Results: Amplicons were observed with a molecular weight of 450bp, 950bp, 800bp, and 650bp respectively as reported earlier. The sequences of these loci were submitted to NCBI. The sequences were approved with accession numbers MN447319, MN733917, MT195537, and MT195538 respectively. The amplified loci of the species and related taxa of the genus were compared using bioinformatics tools. 204 numbers of SNPs/indels were identified out of which some are unique for the species. K2P analysis showed that the maximum intraspecific distance (1.3%) was lower than the minimum interspecific distance (2.6%). Conclusion: Among the different universal barcoding loci, matK was found to be most informative in terms of the occurrence of SNPs and genetic distance. So, the information can be utilized for species authentication in the family Oxalidaceae.
Keywords: Averrhoa carambola; DNA Barcoding; atpF–atpH; matK; rpoB